Evaluation of nested network mobility approaches - Senan, Shayma; Hassan Abdalla Hashim, Aisha; Saeed, Rashid Abdelhaleem; Daoud, Jamal Ibrahim (Asian Network for Scientific Information, 2011)

(untitled)
Due to the fast development of network technologies in the past few years, situations where not only a single node but an entire network roams and changes its point of attachment to the Internet has been revealed. However, an important requirement for any protocol supporting network mobility is to achieve continuous, optimal and secure communication to and from all nodes. Network Mobility (NEMO) developed by IETF is introduced for this purpose but it still suffers from some limitations. The main goal of this research is to study and evaluate the current approaches for mobility support in nested mobile networks. It introduces the main concepts of Mobile IPv6, which NEMO is extended from it and describes the basic functionality of Mobile Networks. More focus is given to nested Mobile Networks. In addition, this research aims to study and present the main approaches and researches done by Internet Engineering Task Force (IETF) regarding NEMO Basic Support. Lastly, discussion and evaluation will be performed on the current researches and protocols that are proposed to overcome the drawbacks of nested NEMO with highlighting their advantages and weaknesses.